A flying start: The long-run effects of inter vivos transfers - Elin Colmsjö (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2024)
This study demonstrates how inter vivos transfers alter the life trajectories of young adults by (i) directly raising wealth levels and (ii) indirectly supporting wealth accumulation by impacting interest rates, borrowing, entrepreneurship, and spending. A unique Danish policy setting allows me to identify intergenerational wealth transfers channeled through initial housing market entries. I find that new entrants receiving a transfer face lower interest rates on non-mortgage debt than general entrants. The advantageous credit position enables recipients to increase their borrowing, used to finance spending and make career-based investments, reflected in a higher propensity to select into entrepreneurship. The treatment effects on borrowing are heterogeneous across gender and education levels, indicating that the impact of transfers on economic and financial outcomes depends on the life situation of the recipient.
Keywords: D31; G51; J62; 330; Intergenerational transmission; wealth; inter-vivos transfers; credit